Glass fiber bulked yarn impregnating compound as well as preparation method, product and application thereof

By using a reasonably proportioned glass fiber wetting agent, the problem of not being easy to disperse and having too many hairs is solved, the noise absorption effect of the car muffler is improved, and the better puffing effect and yarn stiffness are achieved.

CN119285254AActive Publication Date: 2025-01-10JUSHI GRP CO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411410757.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

Smart Images

  • Figure BDA0005077917360000021
    Figure BDA0005077917360000021
  • Figure BDA0005077917360000022
    Figure BDA0005077917360000022
  • Figure BDA0005077917360000031
    Figure BDA0005077917360000031
Patent Text Reader

Abstract

The invention provides a glass fiber bulked yarn impregnating compound for an automobile silencer, the impregnating compound contains solid components and water, the solid components comprise a silane coupling agent A, a silane coupling agent B, a film-forming agent A, a film-forming agent B, a lubricant, a bulking agent, a dispersing agent and a pH value regulator; the mass of the solid component accounts for 3-5% of the total mass of the impregnating compound. The glass fiber produced by coating with the impregnating compound has the advantages of good dispersity, less hairiness, good bulkiness, high temperature resistance, corrosion resistance and good noise absorption effect after puffing processing, and is suitable for producing automobile silencers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass fiber sizing agents, and in particular to a glass fiber bulked yarn sizing agent for automobile mufflers, and a preparation method, product and application thereof. Background Art

[0002] At the beginning of the 20th century, with the rapid development of the automobile industry, the early automobile noise problem attracted people's attention, and automobile manufacturers began to work on solving this problem. In the early 1930s, Calson of Sweden first developed the world's first vibration-isolating silencer, which was a cylindrical silencer made of steel plates. Subsequently, Bickermann of Germany designed the first set of tubular resistive silencers in 1936. This silencer places sound-absorbing materials in the pipe and reduces noise through the principle of resistive sound absorption. In the silencer, glass fiber is usually used as a sound-absorbing material and filled in the silencer shell. The fine fiber structure of glass fiber has good sound absorption performance and can effectively absorb medium and high frequency noise; in addition, glass fiber also has good insulation performance and can avoid electromagnetic interference; due to its good silencing effect, high temperature resistance, and high cost performance, it is still widely used in the field of automobile silencing.

[0003] Glass fiber bulked yarn is a special type of glass fiber. It is produced by compressed air jet method. The continuous glass fiber yarn passes through the bulking deformation nozzle. In the nozzle, it is impacted and disturbed by the turbulence formed by the compressed air, so that the fibers in the yarn are separated and the volume increases to become bulked yarn. When the volume of the bulked yarn increases, the filament loop is formed, while the untwisted roving bulked yarn hardly forms a filament loop and only increases the volume. Due to the processing characteristics of bulked yarn, the bulked yarn has both the high strength of long fiber and the fluffiness of short fiber. It is a new type of material that is harmless to the human body with high temperature resistance, low thermal conductivity, corrosion resistance, high void ratio and high filtration efficiency. It can be widely used in automobile, construction, thermal insulation, sound insulation and other application fields.

[0004] Glass fiber bulked yarn for automobile muffler has the characteristics of being fluffy, resistant to high temperature, and resistant to acid corrosion, and can be used in automobile mufflers. In order to ensure that the automobile muffler has a good silencing effect, the bulked yarn is required to have good bulkiness. At present, domestic bulked yarns are generally sticky, and the bulking production is not easy to disperse, and the bulking effect is poor, resulting in poor silencing effect; secondly, there are more hairiness, the yarn strength is not enough, and it is easy to cause the yarn to break. At present, it is urgent to solve the technical problems such as the difficulty of yarn dispersion, more hairiness, and poor bulking effect. Summary of the invention

[0005] The present application aims to provide a glass fiber bulked yarn impregnating agent for automobile mufflers. The glass fiber produced by coating with the impregnating agent has good dispersion and less hairiness. After the expansion process, it has good fluffiness, high temperature resistance, and corrosion resistance. It has a good noise absorption effect and is suitable for the production of automobile mufflers.

[0006] According to one aspect of the present application, a glass fiber bulked yarn sizing agent for automobile muffler is provided, comprising silane coupling agent A, silane coupling agent B, film former A, film former B, lubricant, dispersant, bulking agent and pH regulator; wherein the solid content of the sizing agent is 3-5%, and the balance is water; the percentage of the solid mass of each component to the solid mass of the sizing agent is expressed as follows:

[0007]

[0008] Preferably, the percentage of the solid mass of each component of the glass fiber sizing to the solid mass of the sizing is expressed as follows:

[0009]

[0010] Further preferably, in the glass fiber sizing agent, the percentage of the solid mass of each component to the solid mass of the sizing agent is expressed as follows:

[0011]

[0012] Wherein, the leavening agent is epoxy polysiloxane.

[0013] Wherein, the silane coupling agent A is an aminosilane coupling agent; and the silane coupling agent B is an epoxysilane coupling agent.

[0014] Preferably, in the glass fiber sizing agent, the mass ratio of the silane coupling agent A to the silane coupling agent B is 1:0.5 to 1:2.

[0015] Wherein, the film-forming agent A is a polyolefin maleic anhydride copolymer with a molecular weight of 3000-8000.

[0016] Wherein, the film-forming agent B is a polyurethane-modified epoxy resin emulsion with an epoxy equivalent of 220 to 350 g / eq.

[0017] Preferably, in the glass fiber sizing agent, the mass ratio of the film-forming agent A to the film-forming agent B is 1:1.5 to 1:4.

[0018] Wherein, the lubricant is a random polyether lubricant.

[0019] Wherein, the dispersant is an ammonium salt cationic dispersant.

[0020] Wherein, the pH value adjuster is acetic acid and / or citric acid; the pH value of the impregnating agent is 3-6.

[0021] In this application, two silane coupling agents are introduced, namely silane coupling agent A and silane coupling agent B. In the process of drawing production, microcracks will be formed on the surface of the glass fiber due to the traction force, and the Si-OH produced by the hydrolysis of the silane coupling agent reacts with the active silanol group on the surface of the glass fiber to form Si-O-Si bonds that can effectively make up for these microcracks and ensure the normal drawing production of the glass fiber. The epoxy silane coupling agent and the amino silane coupling agent are selected to be better compatible with the polyurethane modified epoxy resin film-forming agent, so that the polyurethane epoxy resin film-forming agent can be efficiently coated on the surface of the glass fiber during the glass fiber drawing production. Among them, the aminosilane coupling agent can be selected from γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane or γ-aminoethylaminopropyltrimethoxysilane coupling agent, and the epoxysilane coupling agent is selected from β-(3,4-epoxycyclohexyl)ethyltrimethylsilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane coupling agent or a mixture of several thereof.

[0022] The ratio of silane coupling agent A to silane coupling agent B in this application is very important. Since the production of automobile mufflers requires the glass fiber to be expanded by high-pressure air, it is easy to cause damage to the glass fiber. Studies have found that if the amount of silane coupling agent is too little, the surface of the glass fiber is not fully covered, the microcracks are not adequately compensated, and the glass fiber is prone to breakage during the expansion process; and if the amount of silane coupling agent is too much, it is easy to cause the coupling agent to cross-link, the yarn is not well dispersed during the expansion process, and the expansion effect is poor. Therefore, in this application, the solid mass of silane coupling agent A accounts for 1% to 7% of the solid mass of the sizing agent, preferably 2% to 6%, and further preferably 3% to 5%; the solid mass of silane coupling agent B accounts for 2% to 11% of the solid mass of the sizing agent, preferably 4% to 9%, and further preferably 5 to 8%. In addition, the ratio of silane coupling agent A to silane coupling agent B in this application is also very important. If the amount of silane coupling agent A is too much, it is easy to cause the aminosilane coupling agent to self-polymerize, affecting the dispersibility of the glass fiber and causing poor swelling effect; if the amount of silane coupling agent A is too little, because its reaction activity is relatively strong compared to coupling agent B, it is easy to cause incomplete coating of the glass fiber surface, which also affects the performance of the glass fiber. Therefore, the present application controls the mass ratio of aminosilane coupling agent to epoxysilane coupling agent to be 1:0.5 to 1:2, preferably 1:1 to 1:1.5. Specific, when the mass ratio of aminosilane coupling agent to epoxysilane coupling agent is 1:1.2, the various properties of the glass fiber produced by the sizing prepared in combination with other components can meet the requirements well.

[0023] The film former is the main component of the sizing agent, which mainly plays a protective role on the glass fiber, determines the stiffness and dispersibility of the glass fiber, and also affects the smoothness of subsequent processing. In the present application, the glass fiber sizing agent includes a film former A and a film former B. Among them, the film former A uses a polyolefin maleic anhydride copolymer with a molecular weight of 3000-8000, specifically, it can be a polypropylene maleic anhydride copolymer; the film former B uses a polyurethane modified epoxy emulsion with an epoxy equivalent of 220-350g / eq. The polyolefin maleic anhydride copolymer can make the glass fiber obtain excellent flexibility, elongation, wear resistance, dryness and impact resistance, and can ensure the early bundling of the glass fiber and the dispersibility after tension, and ensure the expansion effect. The polyurethane modified epoxy resin can make the glass fiber have good elasticity, wear resistance and impact resistance, and can also appropriately improve the stiffness of the glass fiber, so that the fluffy nature of the expanded glass fiber is maintained. The amount of the film former A and the film former B needs to be within a suitable range to achieve a relatively good effect. If the amount of polyolefin maleic anhydride copolymer is too large, its hydrolysis will produce a large number of carboxyl groups, which will destroy the stability of the emulsifier in other components, resulting in demulsification and precipitation of the glass fiber sizing agent (for example, glycerol stearate is unstable under strong acid conditions; sodium dodecyl sulfate is easily hydrolyzed into lauryl alcohol and sodium bisulfate in a strong acidic environment, resulting in a decrease in effective ingredients.); if the amount is too small, the glass fiber will be insufficient in toughness and easily break during the high-pressure air expansion process. If the amount of polyurethane modified epoxy resin is too large, the glass fiber will become sticky and affect the expansion effect; if the amount is too small, the stiffness of the glass fiber will decrease, affecting the retention of the fluffiness of the glass fiber after expansion. Therefore, the solid mass of the film-forming agent A of the present application accounts for 8% to 23% of the solid mass of the wetting agent, preferably 10% to 20%, and further preferably 12% to 18%; the solid mass of the film-forming agent B accounts for 34% to 52% of the solid mass of the wetting agent, preferably 37% to 50%, and further preferably 40% to 47%.

[0024] In the present application, the mass ratio of film former A to film former B is controlled to be 1:1.5 to 1:4, preferably 1:2 to 1:3. In particular, when the mass ratio of film former A to film former B is 1:2.8, the properties of the glass fiber produced by the sizing prepared in combination with other components can meet the requirements well.

[0025] In the present application, the lubricant is a random polyether lubricant. The lubricant is a necessary component of the glass fiber impregnation agent. The use of the lubricant can increase the lubrication effect of the glass fiber during the drawing and processing process, reduce the damage to the surface of the glass fiber and the generation of hairiness during the expansion process. The lubricant in the present application is selected from propylene glycol random polyether. Random polyether lubricants have low hygroscopicity, are basically non-toxic and have good dispersibility, have strong emulsifying power, and good low-temperature fluidity; after emulsification, they can be well dispersed in water, can play a good lubricating role, ensure the smoothness of the glass fiber in use, and reduce the generation of hairiness; their low hygroscopicity ensures the dryness of the glass fiber after expansion, maintains the fluffiness of the glass fiber, and ensures the sound-absorbing effect. If the amount of lubricant is too little, it will affect the smoothness of the wire drawing operation, easily cause yarn wear, burrs, yarn breakage and other problems; if the amount of lubricant is too much, it will affect the dispersion of the yarn, and the excess lubricant will adhere to the tension roller and the expanding nozzle. As time goes by, the amount of lubricant adhered to the tension roller and the nozzle increases, and the adhesion increases, which will affect the smoothness of the yarn and the expanding effect. Therefore, the solid mass of the lubricant in this application accounts for 2% to 9% of the solid mass of the impregnating agent, preferably 4% to 7%, and more preferably 5% to 6%.

[0026] In the present application, the leavening agent is a key component, which mainly plays the role of fluffing the yarn and ensuring the puffing effect and fluffiness of the glass fiber. The leavening agent in the present application is epoxy polysiloxane, and the main function of epoxy polysiloxane is to inhibit specific adsorption and improve the separation effect; at the same time, epoxy polysiloxane can also fill the microcracks generated in the process of glass fiber drawing, reduce the generation of hairiness, and can be well soluble with the coupling agent, and increase the stability of the sizing agent. If the amount of leavening agent is too little, it will directly affect the puffing effect of the glass fiber; if the amount of leavening agent is too much, it will not make the glass fiber puffing effect better, but will cause waste and increase production costs. At the same time, too much leavening agent is easy to adhere to the nozzle of the puffing machine, affecting the smoothness and puffing effect of the subsequent use of the glass fiber. Therefore, the solid mass of the leavening agent in the present application accounts for 2% to 9% of the solid mass of the sizing agent, preferably 3% to 7%, and further preferably 4% to 6%.

[0027] In this application, the dispersant is a very important component. The glass fiber sizing agent is a very complex mixed system. Once the mixture of multiple components forms aggregation or even precipitation, it will affect the subsequent drawing smoothness and the uniformity of the sizing agent coating. The addition of the dispersant can play two roles: 1. Promote uniform dispersion and prevent precipitation and aggregation; 2. Reduce the surface tension of the glass fiber, promote the formation of a complete coating between the sizing agent and the glass fiber interface, and improve the dispersibility of the glass fiber. Preferably, the dispersant of the present application adopts an amine salt cationic dispersant. Because a certain negative charge will be generated during the production process of glass fiber, the cationic dispersant can neutralize this part of the negative charge, avoid the yarn bonding caused by electrostatic action, and ensure the dispersibility and smoothness of the yarn. The amount of dispersant is very particular. If the amount is too little, the sizing agent will gradually aggregate and settle over time, and uneven coating will occur, affecting the performance of the subsequent glass fiber; if the amount is too much, the hydrophilicity of the sizing agent will be stronger, reducing the coating effect of the resin particles, and too much dispersant will be a waste after reaching saturation, resulting in an increase in production costs. Therefore, the percentage of the solid mass of the dispersant of the present application to the solid mass of the wetting agent is 10% to 26%, preferably 12% to 23%, and more preferably 14% to 21%.

[0028] In the present application, the pH value adjusting agent can make the coupling agent be better and faster to be uniformly dispersed in water, and at the same time adjust the pH value of the prepared impregnating agent to be controlled in the range of 3 to 6. In the present application, the pH value adjusting agent is acetic acid and / or citric acid, and the solid mass of the acetic acid and / or citric acid accounts for 1% to 6% of the solid mass of the impregnating agent, preferably 1.5% to 5%, and more preferably 2% to 4%.

[0029] The glass fiber sizing agent of the present application introduces coupling agent A and coupling agent B, and the two are used in coordination to effectively protect the glass fiber. The coordinated use of the two film-forming agents can not only ensure the stiffness, dispersibility and flexibility of the yarn, but also improve the bulking effect of the yarn. The use of lubricants ensures the smoothness of glass fiber production and use. The use of bulking agents ensures the bulking effect and fluffiness of glass fibers. The use of dispersants ensures the stability of the sizing agent and also improves the dispersibility of glass fibers. By reasonably matching silane coupling agents, film-forming agents, lubricants, dispersants, pH regulators and water, the glass fiber produced by coating the glass fiber sizing agent is prepared, which has the characteristics of moderate yarn stiffness, easy dispersion, good smoothness of use and good impact resistance, and can well meet the requirements of the bulking production process in the production process, and the performance of the muffler produced by the sizing agent is better than that of conventional products.

[0030] According to another aspect of the present application, a method for preparing the above-mentioned glass fiber sizing is provided, comprising the following steps:

[0031] 1S. Preparation of a silane coupling agent mixed solution: take water with a mass of 30 to 40 times the total mass of silane coupling agent A and silane coupling agent B, add a pH adjuster, and stir for 5 to 10 minutes to obtain an aqueous solution with a pH value of 3 to 6; add silane coupling agent A and silane coupling agent B to the aqueous solution in sequence, and stir for 30 to 40 minutes to obtain a silane coupling agent mixed solution;

[0032] 2S. Dilution of film-forming agent, lubricant, leavening agent and dispersant: stir and dissolve film-forming agent A with 6 to 8 times its weight of water to obtain dissolved film-forming agent A emulsion; stir and dilute film-forming agent B with 2 to 4 times its weight of water to obtain diluted film-forming agent B emulsion; stir and dilute lubricant with 3 to 8 times its weight of water to obtain diluted lubricant aqueous solution, wherein the water temperature is 40 to 50°C; stir and dilute leavening agent with 4 to 7 times its weight of water to obtain diluted leavening agent aqueous solution, wherein the water temperature is 35 to 50°C; stir and dilute dispersant with 5 to 10 times its weight of water to obtain diluted dispersant aqueous solution, wherein the water temperature is 50 to 65°C;

[0033] 3S. Preparation of the wetting agent: Add the diluted film-forming agent A emulsion, film-forming agent B emulsion, lubricant aqueous solution, leavening agent aqueous solution, and dispersant aqueous solution prepared in the step 2S to the silane coupling agent mixed solution prepared in the step 1S, supplement the water in the wetting agent formula, and stir for 25 to 40 minutes to obtain the glass fiber wetting agent.

[0034] According to a third aspect of the present application, there is provided glass fiber produced by coating the above-mentioned glass fiber bulked yarn with a sizing agent.

[0035] According to a fourth aspect of the present application, there is provided application of the above-mentioned glass fiber bulked yarn sizing agent in automobile mufflers.

[0036] Compared with the prior art, the present application has the following beneficial effects:

[0037] 1. The present application uses a compound silane coupling agent and studies a suitable content ratio, which can effectively protect the glass fiber.

[0038] 2. This application studies the combination of film-forming agents in the impregnating agent formula, and uses polyolefin maleic anhydride copolymer and polyurethane modified epoxy resin emulsion in a certain ratio. The coordinated use of the two film-forming agents can make the glass fiber yarn have a suitable hardness, which is more conducive to wire drawing; secondly, it can be naturally spread out during use to ensure the puffing effect.

[0039] 3. The present application innovatively adds a bulking agent, which is used in a certain proportion in the sizing agent, so that the glass fiber has a better bulking effect and fluffiness during the bulking process. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0041] The glass fiber sizing agent of the present application comprises a silane coupling agent, a lubricant, a film-forming agent, and a pH value adjusting agent; wherein the mass of the non-water portion of the sizing agent accounts for 3-5% of the total mass of the sizing agent, and the remainder is water; the percentage of the solid mass of each component to the solid mass of the sizing agent is expressed as follows:

[0042]

[0043] Preferably, the percentage of the solid mass of each component to the solid mass of the infiltrant is expressed as follows:

[0044]

[0045]

[0046] Further preferably, the percentage of the solid mass of each component to the solid mass of the infiltrant is expressed as follows:

[0047]

[0048] Preferably, silane coupling agent A is an aminosilane coupling agent, silane coupling agent B is an epoxysilane coupling agent, and the mass ratio of the two is 1:0.5 to 1:2; film-forming agent A is a polyolefin maleic anhydride copolymer with a molecular weight of 3000-8000, and film-forming agent B is a polyurethane modified epoxy emulsion with an epoxy equivalent of 220 to 350 g / eq, and the mass ratio of the two is 1:1.5 to 1:4; the lubricant is a random polyether lubricant; the leavening agent is epoxy polysiloxane; the dispersant is a cationic dispersant; the pH adjuster is acetic acid and / or citric acid; the pH value of the wetting agent is 3 to 6.

[0049] The preparation method of the glass fiber sizing agent comprises the following steps:

[0050] 1S. Preparation of a silane coupling agent mixed solution: take water with a mass 30-40 times the total mass of silane coupling agent A and silane coupling agent B, add a pH adjuster, and stir for 5-10 minutes to obtain an aqueous solution with a pH value of 3-6; add silane coupling agent A and silane coupling agent B to the aqueous solution in sequence, and stir for 30-40 minutes to obtain a silane coupling agent mixed solution;

[0051] 2S. Dilution of film-forming agent, lubricant, leavening agent and dispersant: stir and dissolve film-forming agent A with 6 to 8 times its weight of water to obtain dissolved film-forming agent A emulsion; stir and dilute film-forming agent B with 2 to 4 times its weight of water to obtain diluted film-forming agent B emulsion; stir and dilute lubricant with 3 to 8 times its weight of water to obtain diluted lubricant aqueous solution, wherein the water temperature is 40 to 50°C; stir and dilute leavening agent with 4 to 7 times its weight of water to obtain diluted leavening agent aqueous solution, wherein the water temperature is 35 to 50°C; stir and dilute dispersant with 5 to 10 times its weight of water to obtain diluted dispersant aqueous solution, wherein the water temperature is 50 to 65°C;

[0052] 3S. Preparation of the wetting agent: Add the diluted film-forming agent A emulsion, film-forming agent B emulsion, lubricant aqueous solution and dispersant aqueous solution prepared in step 2S to the silane coupling agent mixed solution prepared in step 1S, supplement the water in the wetting agent formula, and stir for 25 to 40 minutes to obtain the glass fiber wetting agent.

[0053] Some specific embodiments of the glass fiber sizing of the present application are listed below.

[0054] Example

[0055] It should be noted that Table 1 provides specific examples of the sizing agent for glass fiber of the present application, and in the formula thereof, the amount of each component used is the percentage of its solid mass to the total solid mass of the sizing agent.

[0056] It should be noted that the specific types, contents and compositions of the components selected in Table 1 do not limit the protection scope of the application.

[0057] Table 1 List of specific examples of wetting agents

[0058] Components Example 1 Example 2 Example 3 Example 4 Example 5 Silane coupling agent A 1 2 3 5 5 Silane coupling agent B 2 3 3 6 7 Film former A 22 20 17 15 15 Film former B 35 37 40 42 45 Lubricants 9 8 7 6 5 Leavening agent 2 2 4 6 5 Dispersants 26 23 21 16 15 pH Adjusters 3 5 5 4 3 Total 100 100 100 100 100 Solid content 4.0 4.0 4.0 4.0 4.0

[0059] Table 1 (Continued) List of specific examples of wetting agents

[0060]

[0061]

[0062] In order to better illustrate the present invention, several embodiments are further listed below. The following embodiments define the specific product brand of each component. It should be noted that the following description is used to explain the present invention, but is not intended to limit the scope of the present invention in any way.

[0063] Example A

[0064] The solid content of the impregnant is 4.0%, and the percentage of the solid mass of each component to the total solid mass of the impregnant is expressed as follows

[0065]

[0066] Example B

[0067] The solid content of the impregnant is 4.0%, and the percentage of the solid mass of each component to the total solid mass of the impregnant is expressed as follows

[0068]

[0069]

[0070] Comparative Example

[0071] In order to further demonstrate the beneficial effects of the present application, the prior art bulked yarn sizing agent formula and sizing agent formulas with different ratios are selected as comparative examples for comparison. The specific comparative example formulas and comparative test results are as follows. The content in each comparative example formula is the percentage of the solid mass of each component to the total solid mass of each sizing agent.

[0072] Comparative Example 1:

[0073] The solid content of the impregnant is 4.0%, and the percentage of the solid mass of each component to the total solid mass of the impregnant is expressed as follows:

[0074] Coupling agent: silane coupling agent, γ-methacryloxypropyltrimethoxysilane, product brand A174, 8%;

[0075] Lubricant: Silicone oil, 9%;

[0076] Film former A: epoxy resin emulsion, product brand DSM J129 (DSM), 55%;

[0077] Film former B: polypropylene emulsion, product brand Michem Emulsion 42035A, 19%; cationic surfactant: octadecyl trimethyl ammonium chloride, organic quaternary ammonium salt 1831, 4.5%

[0078] pH adjuster: acetic acid, 3.5%.

[0079] The preparation method of Comparative Example 1 comprises the following steps:

[0080] (1) Add 30% to 40% of the total amount of water to a container equipped with a variable speed stirrer, add a pH adjuster and a silane coupling agent in sequence, and stir until the solution is clear;

[0081] (2) diluting film former A and film former B with water and adding them into a container, wherein the mass of water is 3 to 6 times that of the film former;

[0082] (3) Dilute the lubricant with water and add it to the container, where the mass of water is 5 to 10 times that of the lubricant;

[0083] (4) diluting the surfactant with water and adding it into a container, wherein the mass of the water is 5 to 10 times that of the surfactant;

[0084] (5) Finally, add the remaining amount of water to the container and stir evenly to obtain the finished product.

[0085] Comparative Example 2:

[0086] The solid content of the impregnant is 4.3%, and the percentage of the solid mass of each component to the total solid mass of the impregnant is expressed as follows:

[0087] Coupling agent: silane coupling agent, γ-methacryloxypropyltrimethoxysilane, product brand A174, 11%;

[0088] Film former: epoxy resin emulsion, product brand JS129 (DSM), 65%;

[0089] Lubricant: PEG lubricant, TX-507, 13%;

[0090] Cationic surfactant: organic quaternary ammonium salt, TX-E10, 6%;

[0091] pH adjuster: acetic acid, 5%.

[0092] The preparation method of Comparative Example 2 comprises the following steps:

[0093] (1) Add 30% to 40% of the total amount of water to a container equipped with a variable speed stirrer, add a pH adjuster and a silane coupling agent in sequence, and stir until the solution is clear;

[0094] (2) diluting film former A and film former B with water and adding them into a container, wherein the mass of water is 3 to 6 times that of the film former;

[0095] (3) Dilute the lubricant with water and add it to the container, where the mass of water is 5 to 10 times that of the lubricant;

[0096] (4) diluting the surfactant with water and adding it into a container, wherein the mass of the water is 5 to 10 times that of the surfactant;

[0097] (5) Finally, add the remaining amount of water to the container and stir evenly to obtain the finished product.

[0098] Fiber molding: The prepared sizing agent (Examples 1-10, Example A, Example B and Comparative Examples 1-2) is applied to the glass fiber bulked yarn product, and the glass fiber bulking performance is tested. Among them, the glass fiber drawing process is 4000H platinum leak plate drawing, the line density is 4800tex, and the single fiber diameter is 24 microns. The drying process can adopt tunnel hot air drying and microwave assisted drying, and the drying time is 14.5 hours to obtain a dried glass fiber yarn ball, and the combustible content of the final product is 0.30±0.15%.

[0099] Bulking: The glass fiber yarn is passed through the first winding wheel, the compressed air high-pressure nozzle, the second winding wheel and the winding device in sequence. The speed of the first winding wheel is controlled to be 200m / min, the pressure of the compressed air sprayed by the high-pressure nozzle is 0.6MPa, and the speed of the second winding wheel is 170m / min. Finally, the bulked yarn is wound through the winding and winding device to form a glass fiber bulked yarn.

[0100] Table 2 Performance test results of the embodiments and comparative examples

[0101]

[0102] Table 2 (Continued) Performance test results of embodiments and comparative examples

[0103]

[0104]

[0105] Note: (1) All data are based on 4800tex yarn test; (2) Bulking rate = (number after swelling - number before swelling) / number before swelling * 100%.

[0106] It can be seen from the above examples that by rationally designing the components and the component contents, we can obtain a sizing agent that meets the requirements. Compared with comparative examples 1 to 2, the glass fibers prepared by using examples 1 to 10 and examples A and B described in this application have a bulking rate of more than 4% and a good bulking effect, indicating that the glass fibers have a better bulking effect and fluffiness in the bulking process after adding the bulking agent; especially the glass fibers prepared by examples 4 and 5 have less hairiness, moderate yarn stiffness, and the yarns are very loose after over-tensioning, with a high bulking rate and a good bulking effect.

[0107] In summary, the glass fiber produced by the glass fiber sizing of the present application not only has less hairiness, moderate yarn stiffness, and is easy to disperse, but also has a good bulking effect, meeting the requirements of the muffler.

[0108] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0109] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A glass fiber bulked yarn sizing agent, characterized in that: It includes silane coupling agent A, silane coupling agent B, film-forming agent A, film-forming agent B, lubricant, dispersant, bulking agent and pH regulator; wherein the solid content of the wetting agent accounts for 3-5%, and the balance is water; the percentage of the solid mass of each component to the solid mass of the wetting agent is expressed as follows:

2. The glass fiber bulked yarn sizing according to claim 1, characterized in that: The percentage of the solid mass of each component to the solid mass of the impregnant is expressed as follows:

3. The glass fiber bulked yarn sizing agent according to claim 1, characterized in that: The leavening agent is epoxy polysiloxane.

4. The glass fiber bulked yarn sizing according to claim 1, characterized in that: The silane coupling agent A is an aminosilane coupling agent, and the silane coupling agent B is an epoxysilane coupling agent; The mass ratio of the silane coupling agent A to the silane coupling agent B is 1:0.5 to 1:

2.

5. The glass fiber bulked yarn sizing according to claim 1, characterized in that: The film-forming agent A is a polyolefin maleic anhydride copolymer with a molecular weight of 3000-8000; the film-forming agent B is a polyurethane modified epoxy resin emulsion with an epoxy equivalent of 220-350 g / eq.

6. The glass fiber bulked yarn sizing according to claim 5, characterized in that: The mass ratio of the film-forming agent A to the film-forming agent B is 1:1.5 to 1:

4.

7. The glass fiber bulked yarn sizing according to claim 1, characterized in that: The lubricant is a random polyether lubricant; The dispersant is an amine salt cationic dispersant; The pH adjuster is acetic acid and / or citric acid.

8. The glass fiber bulked yarn sizing according to claim 1, characterized in that: The percentage of the solid mass of each component to the solid mass of the infiltrant is expressed as follows: Wherein, the silane coupling agent A is an aminosilane coupling agent, and the silane coupling agent B is an epoxysilane coupling agent: The film former A is a polyolefin maleic anhydride copolymer with a molecular weight of 3000-8000; the film former B is a polyurethane modified epoxy resin emulsion with an epoxy equivalent of 220-350 g / eq; The lubricant is a random polyether lubricant; The leavening agent is epoxy polysiloxane; The dispersant is an amine salt cationic dispersant; The pH adjuster is acetic acid and / or citric acid.

9. A method for preparing a bulked glass fiber yarn sizing according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1S. Preparation of a silane coupling agent mixed solution: take water with a mass 30-40 times the total mass of silane coupling agent A and silane coupling agent B, add a pH adjuster, and stir for 5-10 minutes to obtain an aqueous solution with a pH value of 3-6; add silane coupling agent A and silane coupling agent B to the aqueous solution in sequence, and stir for 30-40 minutes to obtain a silane coupling agent mixed solution; 2S. Dilution of film-forming agent, lubricant, leavening agent and dispersant: stir and dissolve film-forming agent A with 6 to 8 times its weight of water to obtain dissolved film-forming agent A emulsion; stir and dilute film-forming agent B with 2 to 4 times its weight of water to obtain diluted film-forming agent B emulsion; stir and dilute lubricant with 3 to 8 times its weight of water to obtain diluted lubricant aqueous solution, wherein the water temperature is 40 to 50°C; stir and dilute leavening agent with 4 to 7 times its weight of water to obtain diluted leavening agent aqueous solution, wherein the water temperature is 35 to 50°C; stir and dilute dispersant with 5 to 10 times its weight of water to obtain diluted dispersant aqueous solution, wherein the water temperature is 50 to 65°C; 3S. Preparation of the wetting agent: Add the diluted film-forming agent A emulsion, film-forming agent B emulsion, lubricant aqueous solution and dispersant aqueous solution prepared in step 2S to the silane coupling agent mixed solution prepared in step 1S, supplement the water in the wetting agent formula, and stir for 25 to 40 minutes to obtain the glass fiber wetting agent.

10. A glass fiber produced by coating the glass fiber bulked yarn sizing according to any one of claims 1 to 8.

11. Use of the glass fiber bulked yarn sizing agent according to any one of claims 1 to 8 in automobile mufflers.

Citation Information

Patent Citations

  • Basalt fiber coating film filter material

    CN102228764A

  • Impregnating agent for winding reinforcement medium-alkali glass fiber direct yarns

    CN105174750A

  • Impregnating compound for glass fiber and preparation method, product and application thereof

    CN114873934A

  • Low-adsorbability matte surface cloth as well as preparation process and application thereof

    CN115216972A

  • Glass fiber impregnating compound, preparation method thereof and glass fiber product

    CN117700124A